Changes in Floodplain Vegetation Density and the Impact of Invasive Amorpha fruticosa on Flood Conveyance - Nagy, Judit; Kiss, Tímea; Fehérváry, István; Vaszkó, Csaba (Journal of Environmental Geography, 2018)
Flood conveyance of floodplains is significantly influenced by the riparian vegetation cover, since vegetation affects flow velocity, therefore has a considerable impact on flood height and rate and pattern of sedimentation. However, climate change promotes the spread of invasive species, and their rapid growth results in dense vegetation stands, thus they have a significant impact on floodwater hydraulics. The aims of the present study are (1) to analyse the long-term changes in land-use and vegetation density on the Lower Tisza River, (2) to evaluate the role of the invasive Amorpha fruticosa in increasing vegetation density, and (3) to model the effect of dense floodplain vegetation on flood level and flood conveyance. Long-term (1784-2017) changes of land-use suggest that in natural conditions the study area was occupied by wetlands (92%), thus water covered the area for almost the whole year. In the 19th century, after levee constructions the wetlands were replaced by meadows and pastures (94%), then by the end of the 20th century planted and riparian forests replaced these land-covers. As a result, the mean roughness (0.14) of the floodplain has increased threefold until the early 21st century. Today forests are invaded by Amorpha fruticosa, which increases the vegetation density by 3% in riparian forests, by 23% in forest plantations, and by up to 100% in abandoned pastures and a rable lands. According to the results of HEC-RAS (Hydrologic Engineering Center’s River Analysis System) and CES (Conveyance Estimation System) models, if floodplain vegetation was managed and Amorpha fruticosa was cleared from the floodplain, peak flood level would decrease by 15 cm. Due to dense vegetation, the flood conveyance decreased by 4-6%, and the presence of Amorpha fruticosa reduced the flood flow velocities by 0.014-0.016 m/s. Accordingly, clearance of the floodplain from Amorpha fruticosa would have positive effects on flood protection, since peak flood stages would decrease and flood waves would shorten.